Stronger together: Group incentives and the demand for prevention - Mylène Lagarde; Carlos Riumallo Herl (Tinbergen Institute, 2023)
We study the power of social incentives to increase individuals' investment in preventive health using small financial incentives with group conditionality. In a field experiment in El Salvador, we compare those to equivalent individual incentives. Despite the uncertainty about others' behavior, group incentives are as effective as individual ones and double the demand for prevention. They achieve these effects by increasing communication, peer pressure, and coordination between members to reduce information asymmetry and address behavioral barriers that limit prevention take-up. Incentives leveraging social interactions may act on both present bias and inaccurate beliefs that limit investment in health services.
Keywords: C93; D91; I12; 330